Protection of cardiac cell-to-cell coupling attenuate myocardial remodeling and proarrhythmia induced by hypertension - Egan Benova, T; Szeiffova Bacova, B; Viczenczova, C; Diez, E; Barancik, M; Tribulova, N (Physiological research, 2016)
Gap junction connexin channels are important determinants of myocardial conduction and synchronization that is crucial for coordinated heart function. One of the main risk factors for cardiovascular events that results in heart attack, congestive heart failure, stroke as well as sudden arrhythmic death is hypertension. Mislocalization and/or dysfunction of specific connexin-43 channels due to hypertension-induced myocardial remodeling have been implicated in the occurrence of life-threatening arrhythmias and heart failure in both, humans as well as experimental animals. Recent studies suggest that down-regulation of myocardial connexin-43, its abnormal distribution and/or phosphorylation might be implicated in this process. On the other hand, treatment of hypertensive animals with cardioprotective drugs (e.g. statins) or supplementation with non-pharmacological compounds, such as melatonin, omega-3 fatty acids and red palm oil protects from lethal arrhythmias. The antiarrhythmic effects are attributed to the attenuation of myocardial connexin-43 abnormalities associated with preservation of myocardial architecture and improvement of cardiac conduction. Findings uncover novel mechanisms of cardioprotective (antihypertensive and antiarrhythmic) effects of compounds that are used in clinical settings. Well-designed trials are needed to explore the antiarrhythmic potential of these compounds in patients suffering from hypertension.
Keywords: antiarytmika; omega-3 mastné kyseliny; Antioxidants; Hypertension; konexin 43; Connexin 43; antioxidancia; Fatty Acids, Omega-3; myokard; zvířata; Humans; Melatonin; Myocardium; melatonin; hypertenze; Heart; mezerový spoj; Gap Junctions; Plant Oils; Anti-Arrhythmia Agents; srdce; lidé; oleje rostlin; Animals